Self‐transcendence in cognitively intact nursing‐home patients: a resource for well‐being. (14th August 2012) - Haugan, Gørill; Rannestad, Toril; Hammervold, Randi; Garåsen, Helge; Espnes, Geir Arild
Abstract Aim This article reports an empirical study of self‐transcendence in cognitively intact nursing‐home patients. The aim was to investigate the interrelationships between self‐transcendence and nursing‐home patients' physical, social, emotional and functional well‐being. Background Finding new and alternative approaches to increase well‐being among nursing‐home patients is highly warranted. Self‐transcendence is considered a developmental process of maturity in adulthood and a vital resource for well‐being at the end of life, thus self‐transcendence could be a useful approach. Design Cross‐sectional Method The self‐transcendence scale and the Functional Assessment of Cancer Therapy General (FACT‐G) Quality of Life questionnaire were used. A sample of 202 cognitively intact nursing‐home patients in Mid‐Norway was selected to respond to the instruments in 2008 and 2009. Analysis was applied by means of LISREL 8·8 Structural Equation Modelling. Results A two‐factor construct of self‐transcendence showed that intrapersonal self‐transcendence directly affected functional well‐being and indirectly influenced physical, emotional and functional well‐being. Interpersonal self‐transcendence directly affected social and emotional well‐being. Additionally important influences were disclosed from functional to emotional and from emotional to physical well‐being. Conclusion Finding nursing interventions to enhance both intrapersonal and interpersonal self‐transcendence might benefit nursing‐home patients' overall well‐being. In a holistic perspective of body‐mind‐spirit, this research generates new‐research questions about the pathways between the different dimensions of well‐being in nursing‐home patients, which is important to holistic nursing practice.